Relationship between cardiac ejection fraction and blood pressure in coronary heart patients - Nila Larisse Silva de Albuquerque; Andressa Suelly Saturnino de Oliveira; Jacqueline Mota da Silva; Aline de Aquino de Almeida Peres; Thelma Leite de Araujo (Rev Rene)
Objective: to analyze the existence of a relationship between cardiac ejection fraction during hospitalization with blood pressure values obtained before and during hospitalization in patients hospitalized for coronary disease. Methods: correlational study, with 303 patients with coronary artery disease. Sociodemographic data were obtained through interviews and the clinical parameters consulted in the medical record. Results: of the participants with low systolic blood pressure, 54.0% had decreased cardiac ejection fraction, showing an association (p<0.001). Systolic pressure during hospitalization was not associated with the cardiac ejection fraction (p=0.060). During hospitalization, diastolic blood pressure and the cardiac ejection fraction showed a statistically significant association (p<0.001) that was directly proportional in the female sex. Conclusion: systolic blood pressure lower than 120mmHg is associated with reduced cardiac ejection fraction in coronary arteries. There was a relationship between increased diastolic blood pressure and elevated left ventricular ejection fraction in women with coronary disease.